Analisis eksperimental efek latihan interval intensitas tinggi (HIIT) terhadap VO₂max dan efisiensi pemulihan pada pemain sepak bola - Leo Pratama; Muhammad Saleh; Anggel Hardi Yanto; Wing Prasetya Kurniawan; Andes Permadi (Universitas Nusantara PGRI Kediri, 2025)
HIIT is a fast and effective way to enhance aerobic performance and recovery capacity, particularly in sports such as professional football. This study investigates the impact of structured HIIT training on the aerobic capacity and recovery of professional footballers. This investigation examined the impact of a six-week structured HIIT program on aerobic capacity and post-exercise recovery in professional footballers. 24 male professional players aged 18-22 were randomly assigned to two groups: the HIIT group (n = 12) performed a 4x4-minute interval protocol at 90-95% HRmax with 3-minute active recovery at 60-70% HRmax, while the control group (n = 12) continued football training. Aerobic capacity (VO₂Max) was determined using the Yo-Yo Intermittent Recovery Test Level 1 (YYIR1), whereas HRR and RPE measured recovery. The HIIT group showed a substantial increase in VO₂Max (p < 0.01; d = 1.3) from 49.3 ± 4.1 to 54.8 ± 3.7 mL/kg/min, while the control group showed no significant change (48.9 ± 4.4 to 49.8 ± 4.2; p = 0.21). The HIIT group showed a 17% increase in post-exercise HRR (p < 0.05), indicating faster recovery and greater parasympathetic reactivation. These results suggest that HIIT enhances aerobic endurance and the body's ability to recover quickly after intense activity, helping football players maintain energy, reduce fatigue, and perform effectively in training and matches. This study shows that planned HIIT programs can assist coaches optimize training time and match performance for professional football players.